(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Since the establishment of the Bretton Woods institutional framework in 1944, the World Bank played the lion’s share in development finance globally. Although World Bank initially operated in terms of inter-governmental cooperation in the field of international economic aid, it soon developed the development finance approach that led to the flourishing of Multilateral Development Banks in the 50s. During the 60s and the 70s development finance became increasingly tied to market-based consideration and started to phase out from the governmental sphere, bringing in private actors. The 80s marked the final stage of this evolution, through the role played by the so-called Washington Consensus and the idea that the State should roll-back from development finance as well as from many other aspects of economics. This contribution tries to depict the evolutionary path of development finance and MDBs’ from its original government-oriented activity to a market-driven activity, a dynamic roughly following the evolutionary path of globalization according to the Washington Consensus principles. In the final section the case of Chinese development finance is addressed, trying to assess to what extent a reversal process is at work in partially bringing back development finance activities within the governmental sphere.